The real insights of individual concerns on commitment to change – the government link companies (GLCS) - Abdul Malek, A Tambi; Leonis, Marchalina; Hartini, Ahmad; Johari, Jalil (2017)
This study identifies the real insights of the individual‟s commitment to change during the major organizational change and what are the factors that really motivates them to commit to change. This research used a multiple case studies of a transformation programs embarked by the government-linked companies (GLCs) in Malaysia. It draws upon two-rounds of personal indepth interviews with six participants from six sectors in various levels in the companies. This naturalistic study highlights the employees‟ commitment to change is heavily related to the transformational leadership style. Members of the divisions above all couched their concerns on change commitment to almost equal extents on the authenticity, strong, visionary, and passion leadership that have clear end game for the business. This research helps further delineate relative employees‟ commitment to change dimensions particularly on the organic approach. Moreover, it helps the change agent in developing the right leadership for the right people and for the right change efforts. There are few efforts exist to empirically test the relationship of the key factors to the employees‟ commitment to change, however none attempts have been made in the context of the GLCs and naturalistic settings.